1998
DOI: 10.1021/ma9800313
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Network Topology on Polydomain−Monodomain Transition in Side Chain Liquid Crystalline Elastomers with Cyanobiphenyl Mesogens

Abstract: Orientation behavior of acrylate-based liquid crystalline (LC) networks containing different types of cross-links is studied and discussed. Cross-links incorporated by chemical reaction with cross-linking agent presumably distort LC order, whereas cross-links induced by γ-irradiation preserve and even stabilize the nematic phase. The comparison of the three different series of LC elastomers is given in terms of the macroscopic order parameter dependence on temperature and external mechanical field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 13 publications
(14 reference statements)
1
39
1
Order By: Relevance
“…After complete orientation, a tilt angle is observed that corresponds to the tilt angle of the monodomain sample under uniaxial strain parallel to the director. As mentioned in literature for SCLCEs [2,3] or MCLCEs, [5,13] a spontaneous rising of the order parameter at certain stress thresholds has been observed. Somehow, a minimum stress is required to induce the rearrangement of the mesogens in the range of 10 kPa.…”
Section: Polydomain-monodomain Structure Transformationsupporting
confidence: 57%
See 1 more Smart Citation
“…After complete orientation, a tilt angle is observed that corresponds to the tilt angle of the monodomain sample under uniaxial strain parallel to the director. As mentioned in literature for SCLCEs [2,3] or MCLCEs, [5,13] a spontaneous rising of the order parameter at certain stress thresholds has been observed. Somehow, a minimum stress is required to induce the rearrangement of the mesogens in the range of 10 kPa.…”
Section: Polydomain-monodomain Structure Transformationsupporting
confidence: 57%
“…[1] Besides the differences in the mechanical response, orientational processes from polydomain-to-monodomain (PM) are of interest for the understanding of the formation of anisotropic systems. First experiments on the characterisation of PM transitions were done on smectic-C (SmC) side-chain liquid-crystalline elastomers (SCLCEs) by stress-strain deformations combined with X-ray experiments [2] or by light scattering studies. [3] The first attempts to study PM transitions in main-chain systems were done on the frame of Smectic-A (SmA) main-chain liquid-crystalline thermosets, [4,5] where four distinct regions were found from stress-strain deformations and stress relaxation experiments: [6] a linear viscoelastic deformation, a homogeneous yielding, a strain softening and a strain hardening region.…”
Section: Introductionmentioning
confidence: 99%
“…The polydomain‐to‐monodomain (P–M) transition is a unique and universal feature of liquid crystalline elastomers (LCEs) 1–9. The monodomain structure can be stabilized through secondary crosslinking 10, 11.…”
Section: Introductionmentioning
confidence: 99%
“…Some experiments, for instance those of Zubarev et al [8], the Mitchell [9] group, and our own observations [1], produce order parameter-temperature curves as if an external field were acting. We thus recall, in detail, the classical analysis [2] of what external fields do to the order parameter curve and to the nematic-isotropic transition.…”
Section: Effect Of Fields On the Nematic-isotropic Transitionmentioning
confidence: 99%